Current trends in diagnostic nuclear medicine instrumentation - Fidler, Valentin (Radiology and oncology (Ljubljana), 2000)
Introduction. The basic principles of nuclear medicine imaging instruments aredescribed with the emphasis on multi crystal scintillation and semiconductor gamma cameras, positron emission scanners without detector inter-ring attenuation septa, new detector materials and semiconductor CZT surgical probes for localization of metastases. For the estimation of minimal useful detector diameter the theoretical equation was derived for the 20% lossof absorbed gamma rays at the edge of the detector. Conclusion. Nuclear medicine instrumentation has been passing throgh vigorous development in the last years and will be most likely also in the near future. New detection materials with much better physical characteristics than the standard NaI as regards the stopping power, energy resolutions, fragility, decay time, light output, and density will most likely replace the NaI. It is expected that new imaging devices with several thousands of tiny crystals or semiconductor arrayof small position sensitive areas will improve the sensitivity and specificity of clinical studies. At the same time the small surgical probes made from these materials are also becoming very popular in surgery tracing the regional metastases.
Keywords: diagnostika; Gamma cameras; Instrumentation; medicinski inštrumenti; nuklearna medicina; Radionuclide imaging; razvoj; Tomography, emission-computed; Tomography, emission-computed, single-photon; Trends